Konvergensi Barisan dan Kelengkapan pada Ruang Metrik Parsial Rectangular - Mohamad Ilham Dwi F; Erna Apriliani; Mahmud Yunus (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
The metric space is one of the objects studied in functional analysis. The metric space has undergone many developments, some eHamples of which are partial metric spaces and rectangular metric spaces. The difference between the metric space and the partial metric space can be seen in the distance of a point from itself. In the metric space, it is always equal to zero, while in the partial metric space it is not equal to zero. On the other hand, the difference between a metric space and a metric rectangular space can be seen in the inequalities used. In the metric space we use triangular inequalities, while in the metric rectangular space we use rectangular inequalities. Shukla in 2014 presents the development of another metric space called rectangular partial metric space, which combines the concept of partial metric space with rectangular metric space. This research we discusses the problem of the properties of the rectangular partial metric space, including convergence sequences, Cauchy sequences, and completeness of space in the rectangular partial metric space.